Formulation and Evaluation of Pluronic F-127 Assisted Carboplatin Cubosomes - Alamoudi, Jawaher Abdullah; Almoshari, Yosif; Alotaibi, Hadil Faris (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The objective of this study was to prepare carboplatin loaded cubosomes using high sheer homogenization technique. Materials and Methods: The cubosomes were prepared using Glyceryl Monooleate (GMO) as a lipophilic carrier along with pluronic F-127 (PF-127) and tween 80 as additive of the formulation. All the ingredients were subjected to chemical compatibility studies by Fourier Transform Infra-Red (FTIR) spectroscopy, thermal analysis using Differential Scanning Calorimetry (DSC), whereas X-ray Diffraction (XRD) studies were performed to evaluate the nature of drug in pure form as well as in formulation. The prepared cubosomes were characterized for their size and surface charge, surface morphology, drug release studies and drug permeation studies. Results: FTIR has confirmed the chemical compatibilities of the ingredients, while DSC has exhibited the thermal stabilities of the drug in alone as well as in cubosomes. The XRD has reviled that drug was crystalline, but upon incorporation in cubosmes, the crystallinity has reduced remarkably. The prepared cubosomes were of nanosized (diameter of 227 nm) and cubical in shape. The in vitro drug release and drug permeation studies have showed that concentration of both GMO and PF-127 has effected the release as well as permeation of the drug. However, in 3 hr studies the maximum amount of drug release was ~84% and that of permeation was ~74%. Conclusion: Conclusively, the selected composition of the formulation was suitable enough to prepare the nanosized cubosomes showing suitable entrapment efficiency of the drug.
Keywords: Anticancer; Cubosomes; in vitro drug release; in vitro permeation studies